A critical assessment of the United States' National Security Strategy and its impact on Latin America (Revista da Escola de Guerra Naval, 2023)
The National Security Strategy (NSS) are specific documentsprepared periodically by the United States’ executive,describing the main concerns of Americans’ national securityand developing strategies to face the challenges. At the sametime, by exposing the US government’s strategic vision, itcontributes to informing the US government’s approachand intent on various topics related to security and foreignpolicy. This paper seeks to analyze the NSS of the last fourAmerican presidents, in a time frame that runs from theimmediate post-Cold War to Trump’s administration, aswell as its influences with regard to Latin America. Usinga quantitative method, through the frequency contentanalysis, and a qualitative methodology, based on theempirical-deductive method, the central objective is torationalize that, although there was a relative power vacuumat the beginning of the 21 st century, there is a return of theregion as an important geopolitical and geoeconomic spacein contemporary times.